The Effect of Product Differentiation and Positioning on Purchasing Decisions for Honda Vario 160 Motorbikes in North Cikarang - Ririn Uke Saraswati; Sarmin Sarmin; Cahyana Cahyana (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
Purchasing decisions are the stage where consumers make purchases after considering various alternatives. This study aims to determine the effect of product differentiation (X1) and positioning (X2) on purchasing decisions (Y) Honda Vario 160 motorbikes in North Cikarang District. Quantitative research method with an associative approach. The number of samples in this study were 97 using Cocran's formula and the sampling technique used was Non Probability sampling, namely Incidental Sampling. Data collection techniques using questionnaires. The data analysis technique uses multiple linear regression analysis with the help of SPSS Version 25. The results of the multiple linear regression equation are Y = 26.569 + 0.218 X1 + 0.382 X2 + e. The results of testing the differentiation variable parcially. The results of testing the differentiation variable partially affect the purchase decision Positioning partially affects the decision Simultaneous testing of the F value count 57.994> F table 3.09 with a significance of 0.00 <0.05 means that the independent variables of differentiation and positioning simultaneously have a significant effect on the purchasing decision variable. The coefficient of determination shows that the two variables contribute 55.8% to purchasing decisions, while the remaining 44.2% of other variables not examined in this study.